Privatization in Transition Countries : Lessons from the First Decade - Havrylyshyn, Oleh.; McGettigan, Donal (Washington, D.C. : International Monetary Fund, 2000)
A decade ago, with the breakup of the Soviet Union and the start of market-oriented reforms in many former socialist economies of Central and Eastern Europe, the prospect of privatizing inefficient state-owned companies figured prominently in both popular and academic writings. As the headline event symbolizing change from central planning to capitalism, privatization seemet to promise an end to the inefficiencies of central planning- the key to freeing the resources and talents of this huge area and lifting its living standards to those of the industrial countries. What broad lessons were learned from the experience of the past ten years? Along with their successes, prominent failures have also marked this recent history, especially in Russia and in other countries of the former Soviet Union. The overall task ahead thus remains vast if the original vision of greater freedom and higher living standards is to be realized.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Investment Decisions; Portfolio Choice